1954
DOI: 10.1104/pp.29.1.82
|View full text |Cite
|
Sign up to set email alerts
|

Applicability of Poiseuille'S Law to Exudation of Oleoresin from Wounds on Slash Pine

Abstract: PLANT PHYSIOLOGY periments in which we have confirmed the observation by Galston and Baker (2) that elongation in the dark of green pea stem segments is much more dependent upon sucrose than is the elongation of etiolated stem segments. Furthermore, since we have detected no promotion by cobalt of the growth of the green segments, the condition affected by cobalt apparently is not limiting to elongation. In one experiment, the elongation of such stem segments (originally 5.3 nun long) was L52 mm on 10 mg/l IAA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
2

Year Published

1973
1973
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 2 publications
1
24
2
Order By: Relevance
“…Trees that have a larger defense infrastructure in xylem may be better at surviving herbivore attack by having a greater capacity to produce, store, and transport oleoresin (Hodges et al 1985, Franceshi et al 2005. Most (Schopmeyer et al 1954;Blanche et al 1992) but not all (Lombardero et al 2000) empirical studies have reported a positive correlation between oleoresin flow or mass; and resin duct size or abundance. While environmental factors (e.g., soil moisture, temperature; Blanche et al 1992;Gaylord et al 2007) often explain considerable variation in tree resin flow, such factors were controlled by the paired tree comparisons in our study.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Trees that have a larger defense infrastructure in xylem may be better at surviving herbivore attack by having a greater capacity to produce, store, and transport oleoresin (Hodges et al 1985, Franceshi et al 2005. Most (Schopmeyer et al 1954;Blanche et al 1992) but not all (Lombardero et al 2000) empirical studies have reported a positive correlation between oleoresin flow or mass; and resin duct size or abundance. While environmental factors (e.g., soil moisture, temperature; Blanche et al 1992;Gaylord et al 2007) often explain considerable variation in tree resin flow, such factors were controlled by the paired tree comparisons in our study.…”
Section: Discussionmentioning
confidence: 93%
“…While environmental factors (e.g., soil moisture, temperature; Blanche et al 1992;Gaylord et al 2007) often explain considerable variation in tree resin flow, such factors were controlled by the paired tree comparisons in our study. By applying Poiseuille's law, with some modification (Schopmeyer et al 1954), small increases in resin duct width should increase oleoresin flow by the power of four. For instance, our study demonstrated that living trees had 13% wider resin ducts than dead trees.…”
Section: Discussionmentioning
confidence: 99%
“…This was less pronounced in the first year in Armuña, probably because the trees had not been tapped before (Rodríguez-García et al, 2014). During the first 15 days after wounding, the resin canal network preformed in the tree the previous year (constitutive and traumatic axial and radial resin canals) connected to the wounded zone starts to empty its contents under the effects of pressure and temperature (Schopmeyer et al, 1954;Lewinsohn et al, 1991) and the de novo resin synthesis process is activated 3-4 days after wounding (Ruel et al, 1998;Lombardero et al, 2000), although in P. taeda some studies have not been able to detect an induced resin flow with mechanical wounding alone (i.e., Klepzig et al, 2005). Resin flow decreases with the sealing of the small radial canals.…”
Section: Intra-annual Analysismentioning
confidence: 99%
“…More resin duct area may result in a larger reservoir of resin available to pitch out invading pests [27], but small resin ducts may also result in reduced resin flow (i.e., rate of resin delivered). Following Poiseuille's law, decreases in resin duct size should decrease resin flow by the fourth power [69]. This increase in resistance to resin flow may partially explain observations of decreased resin flow with greater competition [70] but requires more direct examination.…”
Section: Defense Relationships With Climate and Competitionmentioning
confidence: 97%